Acceptability and outcomes of percutaneous endoscopic gastrostomy (PEG) tube placement and patient quality of life - Somi Mohammad HOSSEIN; Maghbouli LEILI; Antikchi Mohammad HOSSEIN (Turkish Journal of Gastroenterology, 2019)
-